Effect of impaired twitching motility and biofilm dispersion on performance of Pseudomonas aeruginosa-powered microbial fuel cells. (1st February 2018) - Shreeram, Devesh D; Panmanee, Warunya; McDaniel, Cameron T; Daniel, Susan; Schaefer, Dale W; Hassett, Daniel J
Abstract: Pseudomonas aeruginosa is a metabolically voracious bacterium that is easily manipulated genetically. We have previously shown that the organism is also highly electrogenic in microbial fuel cells (MFCs). Polarization studies were performed in MFCs with wild-type strain PAO1 and three mutant strains ( pilT, bdlA and pilT bdlA ). The pilT mutant was hyperpiliated, while the bdlA mutant was suppressed in biofilm dispersion chemotaxis. The double pilT bdlA mutant was expected to have properties of both mutations. Polarization data indicate that the pilT mutant showed 5.0- and 3.2-fold increases in peak power compared to the wild type and the pilT bdlA mutant, respectively. The performance of the bdlA mutant was surprisingly the lowest, while the pilT bdlA electrogenic performance fell between the pilT mutant and wild-type bacteria. Measurements of biofilm thickness and bacterial viability showed equal viability among the different strains. The thickness of the bdlA mutant, however, was twice that of wild-type strain PAO1. This observation implicates the presence of dead or dormant bacteria in the bdlA mutant MFCs, which increases biofilm internal resistance as confirmed by electrochemical measurements.